(untitled) (Annals of Medical Research, 2021)
Ovarian hyperstimulation syndrome (OHSS) caused by controlled ovarian hyperstimulation ,although usually regressing spontaneously, may occasionally occur with clomiphene citrate, typically with gonadotropin, which sometimes results in serious complications. 25-year-old patient was followed up in our hospital due to OHSS. Since our patient was Clomiphene Citrate (CC) resistant Polycystic ovary syndrome (PCOS), follitropin alpha was started. Firstly, treatment started from 75 IU rFSH. Increased to 150 IU on day 15, if no improvement in the ovaries. Due to the development of two 18 mm follicles on the 21 st day and the E2 value being 773 pg/mL, human chorionic gonadotropin (hCG) was applied and insemination was performed. Patients with CC resistant PCOS represent a challenge for reproductive medicine. We propose a calculated low-dose stimulation strategy with step- up according to ovarian response in gonadotropins protocols. If the treatment period is extended and the dose is increased; Even if the follow-up values are normal, the patient should be closely monitored to avoid OHSS.